JALUR KHUSUS SEPEDA MOTOR - Hikmat Iskandar (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
Traffic accident occurrences in Indonesia have usually been published in many public media. In year 2003, police reported more or less 14,000 occurrences have been noted. Out of them, about 80% involved motorcycle. This high portion demands real and immediate countermeasures. Learn from experiences of neighborhood countries, motorcycle are splitting from other motorized vehicle into special lanes, called special lane for motorcycles (LKSM). This type of lanes, although, has been implemented in several lanes or highway in Indonesia, it is used locally, not standardized road. Laws No.38-2004 about Roads and its following regulation No.34-2006, does not regulate special lane for motorcycle, nor in technical codes. The type of LKSM implemented in locals are: a) the use of shoulder for LKSM, with additional improvement; b) used of the most left lane on multi lanes road for LKSM; and 3) provision of exclusive lanes for motorcycle with special geometric and designed to meet motorcycle requirement. This paper aims to discuss possibility to implement LKSM in Indonesian public roads, noted the need of the basic laws, study on motorcycle flow characteristics, geometrics, traffic codes, campaign, and law enforcement. Keywords : Road Geometry, Motorcycle Lane